Managerial economics : (W.W. Norton, 2005)
Through five editions, Managerial Economics has been among the leading texts in the field. Maintaining its hallmark clarity, abundant use of real-world examples and cases, and strong coverage of international issues and technological change, the Sixth Edition has been rigorously updated and revised, adding six entirely new chapters and an innovative student Web site